Pengembangan Bahan Ajar Biologi Berbasis Jelajah Alam Sekitar (JAS) Berorientasi pada Keterampilan Proses Sains Siswa dan Hasil Belajar Siswa Kelas X SMA - Royani, Ida; Imran, Ali; Dharmawibawa, Iwan Doddy (Bioscientist : Jurnal Ilmiah Biologi, 2023)
The aim of the research is to determine the validity, practicality and effectiveness of the use of Environmental Exploration (EE)-based biology teaching materials which are oriented towards science process skills and learning outcomes for class X students at SMA Al-Hamzar Tembeng Putik, East Lombok Regency. The background of this research is the lack of direct use of learning resources from nature, learning resources only come from books provided by the school. The subjects in this research were class Xc students. The type of research carried out is Development Research (DR). The results of content feasibility validation obtained an average value of 3.08 in the valid category. Validation on the presentation aspect obtained an average of 3.21 which is included in the valid category. Validation on the language aspect obtained an average of 2.88, including the valid category. Judging from the graphic aspect, an average of 3 is found to be in the valid category. If the validity index is averaged, overall the aspects assessed at 3.04 are categorized as valid with an increase in children's learning outcomes in terms of students' attitudes, knowledge and science process skills. The conclusion of this research is that biology teaching materials in the form of Environmental Exploration (EE) based modules are declared valid and can be used as biology teaching materials in class experiment, measure, draw conclusions, and communicate the learning outcomes of class X students at SMA Al-Hamzar Tembeng Putik, East Lombok Regency.